Pengaruh Price Discount dan Bonus Pack terhadap Impulse Buying melalui Nilai Hedonik di Carrefour Surakarta - Sri Isfantin Puji Lestari (Universitas Proklamasi 45 Yogyakarta, 2018)
The purpose of this study is to analyze the Price Discount and Bonus Pack to the Hedonic Shopping Value as well as its impact on Impulse Buying of Carrefour customers in Surakarta. The results of this study show that the price discount and bonus pack have influence on hedonic shopping value and impulse buying. This study also shows that the hedonic shopping value is an intervening variables that can mediate the effect of price discount and bonus pack variables on impulse buying.